Sodium butyrate in both prevention and supportive treatment of colorectal cancer - Kaźmierczak-Siedlecka, Karolina; Marano, Luigi; Merola, Elvira; Roviello, Franco; Połom, Karol (Frontiers in Cellular and Infection Microbiology, 2022)
Accumulating evidence suggests that selected microbiota-derived metabolites play a significant role in both tumor prevention and supportive treatment of cancer. Short-chain fatty acids (SCFAs), i.e., mainly acetate, proprionate, and butyrate, are one of them. Nowadays, it is known that butyrate is a key microbial metabolite. Therefore, in the current review, we focused on butyrate and sodium butyrate (NaB) in the context of colorectal cancer. Notably, butyrate is characterized by a wide range of beneficial properties/activities. Among others, it influences the function of the immune system, maintains intestinal barrier integrity, positively affects the efficiency of anti-cancer treatment, and may reduce the risk of mucositis induced by chemotherapy. Taking into consideration these facts, we analyzed NaB (which is a salt of butyric acid) and its impact on gut microbiota as well as anti-tumor activity by describing molecular mechanisms. Overall, NaB is available as, for instance, food with special medical purposes (depending on the country’s regulation), and its administration seems to be a promising option for colorectal cancer patients.